Contribution to the flora of Asian and European countries: new national and regional vascular plant records, 8. Issue 2 (3rd April 2019) - Nobis, Marcin; Klichowska, Ewelina; Terlević, Ana; Wróbel, Anna; Erst, Andrey; Hrivnák, Richard; Ebel, Aleksandr L.; Tikhomirov, Valery N.; Byalt, Vyacheslav V.; Gudkova, Polina D.; Király, Gergely; Kipriyanova, Laura M.; et al.
ABSTRACT: The paper presents new records of 24 vascular plant species from 11 Eurasian countries. One taxon ( Orobanche laxissima ) is reported from Armenia; one ( Epipactis condensata ) from Azerbaijan; two ( Phragmites americanus, Polygala multicaulis ) from Belarus; one ( Stipa caucasica ) from Egypt; one ( Puccinellia hauptiana ) from Kyrgyzstan; three ( Aquilegia xinjiangensis, Geranium saxatile, Ranunculus songaricus ) from Mongolia; one ( Stipa roborowskyi ) from Pakistan; three ( Echinochloa muricata, Erigeron acris subsp. podolicus, Hypericum majus ) from Poland; six from Russia, whereof one ( Zanthoxylum armatum ) from the European part of Russia and five ( Chaerophyllum aureum, Elsholtzia densa, Poa compressa, Ranunculus subrigidus, Viola sororia ) from the Asian part of Russia; two ( Ludwigia repens, Sagittaria latifolia ) from Slovakia; and three ( Rubus ambrosius, Rubus camptostachys, Rubus perrobustus ) from Ukraine. For each species, synonyms, general distribution, habitat preferences, taxonomy with remarks on recognition and differentiation of the species from the most similar taxa occurring in a given country, as well as a list of recorded localities (often far from the previously known areas), are presented.